A multi-dimensional energy-based analysis of neighbourhood sustainability assessment tools: are institutional indicators really missing?. Issue 5 (4th July 2021) - Dawodu, Ayotunde; Cheshmehzangi, Ali; Sharifi, Ayyoob
ABSTRACT: The popularity of Neighborhood Sustainability Assessment Tools (NSATs) has grown over the past decade, which has led to the replications of these tools in different regions but also their limitations. One of the most notable limitations is the inadequate recognition of the complexities of the institutional dimensions (i.e. policies, laws, and regulation) that contribute to mainstreaming and operationalizing sustainable neighborhood development. Although existing research on NSATs suggest lack of coverage of the institutional dimension of sustainability, there has been no consistent and explicit mention of the precise institutional indicators and criteria in literature. Also, there is a clear confusion regarding what are the institutional indicators, what characteristics they possess, and how best they can be identified. This study, via the lens of energy-based indicators, expands on the role and trends of the institutional indicator and its associated dimensions in 15 NSATs. The results show a limited view on the classification of institutional indicators. The study also demonstrates there are more institutional indicators than previously reported in prior studies. Finally, this study proceeds to define more appropriately what can be considered an institutional indicator. In conclusion, it is recommended that future development of NSATs should ensure a constant institutional link to indicators in order to enhance the performance of NSATs..